Vector Control and Personal Protection Measures Practiced at Household Level by Tribal and Non-Tribal Communities in A Rural Area of Kamrup District, Assam - Phukan, Purabi (National Journal of Community Medicine, 2012)
Background: Vector Control and Personal Protection measures practices play major role in control of malaria. Objective: The study objective was to find out the practices of mosquito control and personal protection measures observed at household level and the acceptance of vector control measures under malaria control programme. Methods: A Community based cross-sectional study was undertaken from June 2009 to May 2010 and 150 tribal and 150 non-tribal head of the households interviewed. Data was collected on socio-demographic characteristics, factors related to mosquito breeding and its prevention practice, personal protection measures, DDT spray status of their houses. Data was analyzed by Epi Info Version7. Results: The overall coverage of DDT was low (25.3%). Coverage was slightly better among tribal households (31.3%) compared to non-tribal population (19.4%). The acceptance of DDT spray was found to be significantly associated with knowledge about mode of transmission of malaria and type of house. Room-wise coverage was not as per norms. Refusal of DDT was seen more among non-tribal communities. Commercial personal protection practices like mosquito repellants, mats and coils were lesser among the tribal counter parts and it was associated with level of income. Majority of tribal and non-tribal respondents were not having knowledge of the new insecticide treated bed nets (ITNs) and LLINs. Conclusion: Coverage with IRS in rural areas is far less (25.3%) than the recommended coverage of 80% required for its effectiveness. With majority using mosquito nets in their houses, use of ITNs should be encouraged and IEC activities for creating greater awareness on methods to control vector population suggested for success of the malaria programme.